Category of Addressee in New Apostolic Prayer: Categorical-Textual and Axiological Aspects - A. I. Keler (Научный диалог)
The study examines the realization of the addressee category in Protestant — New Apostolic prayers. The object of analysis is prayer as a genre of religious functional style, and the subject is the addressee category. The aim of the work is to describe the ways of explication of the addressee category in a corpus of 220 public prayers of New Apostolic Christians. The textual material was collected through participant observation and consists of transcribed audio recordings of prayers — non-reproducible texts spontaneously created by both churchgoers and clergy in various communicative situations, both religious and non-religious. The methodology of constructing thematic nomination chains is applied on a categorical-textual basis to describe the addressee category. It has been revealed that the addressee is denoted using personal pronouns ‘we’, possessive pronoun ‘our’, and nouns ‘community’, ‘brothers and sisters’, ‘children’, ‘sinners’. The results of the analysis show that these nominations are included in positively colored contexts, including the nomination ‘sinners’, which is conditioned by the specificity of the doctrine: the praying individuals are focused not on repentance but on gratitude for forgiveness. The listed ways of nominating the addressee and the description of evaluative contexts allow us to conclude about the reflection of ‘we axiological’ in the texts of New Apostolic Christians.